Réponses

Meilleure réponse !
2014-10-30T14:11:31+01:00
Bonjour

a) 105 ² = 11 025
b) 97 x 103 = 9 991
c) (x +3)² = x² + 6 x +9
d) (3 +4 x)² = 9 + 24 x + 16 x²
e) (4 x -8)² = 16 x² - 64 x + 64
f) (2 - 3 x)² = 4 - 12 x + 9 x²
g) (x + 5) ( x -5) = x ² - 25
h) (3 -4 x) ( 3 +4 x) = 9 - 16 x²
i) ( x + 2)( 3 - 5x ) + ( 3 x -2)(3 x +2) = 3 x - 5 x² + 6 - 10 x + 9 x² - 4
= 4 x² - 7 x + 2
2014-10-30T14:11:43+01:00
C =(x+3)² = x²+6x+9

d =(3+4x)² = 9 +24x +16x²

e = (4x-8)² = 16x² -64x +64

f =(2-3x)² = 4 -12x +9x²

g = (x+5)(x+5) = (x+5)² = x²+10x+25

h = (3-4x)(3+4x) 9 -16x²

i = (x+2)(3-5x) +(3x-2)(3x+2)
i = 3x-5x²+6 -10x +9x²-4
i =  4x² -7x +2